The hausa of Nigeria - Salamone, Frank A. (University Press of America, 2010)
This book is the culmination of thirty-nine years of anthropological thought and research and many field trips to Nigeria. This work looks at the notion of identity formation and its relationship to history, religion, warfare, gender, economics, various other dimensions of Hausa life, minority group relationships, and creolization